Peran Guru Bimbingan dan Konseling dalam Menangani Permasalahan Peserta Didik Berbasis Teori Erikson dan Pendekatan Carl Rogers - Mas'ady Ashabul Kahfi; Roudhoh Binuchillah; Wiwin Luqna Humaida (ALSYS, 2025)
The limited number of studies examining the role of Guidance and Counseling (GC) teachers in identifying and addressing student issues at the junior high school level forms the background of this research, considering that early adolescence is a critical phase prone to identity crises, academic decline, and social conflict. This study aims to analyze the roles, strategic approaches, and challenges faced by GC teachers in addressing student problems at SMPN 3 Waru. A qualitative approach with a case study design was employed. Participants included GC teachers, homeroom teachers, and students selected through purposive sampling. Data were collected through in-depth interviews, direct observation, and documentation, and analyzed using thematic analysis techniques. The findings reveal that GC teachers play a central role in identifying student issues through observation, coordination with teachers and parents, and personal interviews. Individual and group counseling were the main strategies employed, supported by home visits in specific cases. The primary challenges included limited counseling staff, constrained service time, and delays in information from both the school and family environments. These findings affirm the relevance of Erik Erikson’s psychosocial development theory in explaining identity crises among adolescents and highlight the effectiveness of Carl Rogers’ client-centered approach in fostering empathetic and meaningful counseling relationships. The study concludes that strengthening school-based GC services should be grounded in humanistic and collaborative approaches. The implications include the need for systemic policy support for the role of GC teachers and the potential for future research employing comparative or longitudinal designs.